Pengukuran Kinerja Sofyan Inn Hotel UNISI Yogyakarta dengan Pendekatan Maslahah Scorecard (MasSC) - Yolanda, Agnes (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2020)
This research aims to observe and describe the orientation of Maslahah in Sofyan Inn Hotel UNISI Yogyakarta. The measurement of the performance process and the performance of the result of Sofyan Inn Hotel UNISI Yogyakarta was conducted through Maslahah Scorecard (MaSC) approach. This is a qualitativedescriptive research with the type of field research. The data were collected using the method of observation, documentation and interview in which the results of this were measured and analyzed using Maslahah Scorecard (MaSC) approach Maslahah scorecard (MaSC)is a assessment tool developed by Ahmad Firdaus measuring the performance of an organization through two phases: assessing the business in achieving the Maslahah (process performance) and assessing the outputs of the Maslahah performance (performance of output). The results of this research showed that Sofyan Inn Hotel UNISI Yogyakarta has implemented six orientations of benefit (Maslahah) including the orientation of worship, orientation of internal process, orientation of talent or workforce, orientation of learning, orientation of customers, and orientation of wealth. In the performance of process in Sofyan Inn Hotel UNISI Yogyakarta it obtained the score of 0.780 and in the performance of the output of the Sofyan Inn Hotel UNISI Yogyakartait obtained the score of 0,994